2013
DOI: 10.12998/wjcc.v1.i7.212
|View full text |Cite
|
Sign up to set email alerts
|

Ingested bone fragment in the bowel: Two cases and a review of the literature

Abstract: Generally, ingested foreign bodies are excreted from the digestive tract without any complications or morbidity. In adults, ingestion of foreign bodies frequently occurs in alcoholics and elderly individuals with dentures. The most commonly ingested foreign bodies are food stuffs or their parts, such as fish bones or fragments of bone and phytobezoars. Sharp foreign bodies like fish and chicken bones can lead to intestinal perforation and peritonitis. We report herein two cases, one of bowel perforation and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Similarly; foreign bodies such as needles, which are put in the mouth during free-time or occupational activities, can also be ingested unintentionally. 3 In the case that presented in this study, the patient had no history of swallowing a foreign object. Ingested foreign bodies are mostly removed out of the body through the digestive system without causing any problems.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly; foreign bodies such as needles, which are put in the mouth during free-time or occupational activities, can also be ingested unintentionally. 3 In the case that presented in this study, the patient had no history of swallowing a foreign object. Ingested foreign bodies are mostly removed out of the body through the digestive system without causing any problems.…”
Section: Discussionmentioning
confidence: 86%
“…It is reported that 95%patients present with abdominal pain as the most important symptom, 81% patients develop fever, and 39% have local peritonitis. [7] …”
Section: Discussionmentioning
confidence: 99%
“…Some of these foreign objects will pass on their own; however, Seyfi et al [ 9 ] reported that 1% of complicated IFB cases required surgical operation, whereas 10–20% of bony particles (especially at the anorectal region) were removed via proctosigmoidoscopy and endoscopy.…”
Section: Discussionmentioning
confidence: 99%